Diversity Analysis of 53 Soybean Accessions Introduced from China Based on Morphological Characteristics and SSR Markers - Dyah, Rosliana Purwaning; Wibisono, Kunto; Terryana, Rerenstradika Tizar; Nugroho, Kristianto; Utari, Ratna; Suparjo, Suparjo; Umar; Lestari, Puji; Tasma, I Made (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
Indonesia still faces challenges in meeting its national soybean demand. Genetic diversity can provide new resources to improve soybean production and quality. Genetic diversity of 53 soybean accessions introduced from China, based on morphological characteristics and 17 SSR markers, was analyzed in this study. Principal component analysis (PCA) conducted on morphological characters produced a total diversity value of 64.67% and identified four main components. Based on phylogenetic analysis and principal coordinate analysis (PCoA) two accessions showed low genetic similarity of 78% (China cult-55 and Mi yang niu mao huang), which indicated that they could be selected as parents for plant breeding programs. In addition, 772 SSR alleles at an average of 45 alleles per locus were detected. The average heterozygosity was 0.83, and the average polymorphic information content (PIC) value was 0.96. All SSR markers showed a PIC value > 0.8, indicating their informativeness in analyzing genetic diversity of soybean. The phylogenetic analysis indicated a genetic similarity of 82% and the accessions were grouped into two main clusters. The phylogenetic analysis depicted that several accessions could be grouped based on the growth type and origin. The results of morphological characterization and molecular markers in the analysis of genetic diversity are beneficial for selecting parental crosses when developing new varieties.